Statins Increase the Bioavailability of Fixed-Dose Combination of Sofosbuvir/Ledipasvir by Inhibition of P-glycoprotein - Abdelkawy, K.S.; Belal, Fathalla; Abdelaziz, AbdelazizE; Elmekawy, H. A.; Abdelgaied, M. Y.; El-Khodary, N. M. (Drug Research, 2022)
Background Coadministration of statins and direct acting antiviral agents is frequently used. This study explored the effects of both atorvastatin and lovastatin on pharmacokinetics of a fixed-dose combination of sofosbuvir/ledipasvir “FDCSL”.Methods 12 healthy volunteers participated in a randomized, three-phase crossover trial and were administered a single atorvastatin dose 80 mg plus tablet containing 400/90 mg FDCSL, a single lovastatin dose 40 mg plus tablet containing 400/90 mg FDCSL, or tablets containing 400/90 mg FDCSL alone. Liquid chromatography-tandem mass spectrometry was used to analyze plasma samples of sofosbuvir, ledipasvir and sofosbuvir metabolite “GS-331007” and their pharmacokinetic parameters were determined.Results Atorvastatin caused a significant rise in sofosbuvir bioavailability as explained by increasing in AUC0−∞ and Cmax by 34.36% and 11.97%, respectively. In addition, AUC0-∞ and Cmax of GS-331007 were increased by 73.73% and 67.86%, respectively after atorvastatin intake. Similarly, co-administration of lovastatin with FDCSL increased the bioavailability of sofosbuvir, its metabolite (AUC0-∞ increase by 17.2%, 17.38%, respectively, and Cmax increase by 12.03%, 22.24%, respectively). However, neither atorvastatin nor lovastatin showed a change in ledipasvir bioavailability. Hepatic elimination was not affected after statin intake with FDCSL. Compared to lovastatin, atorvastatin showed significant increase in AUC0-∞ and Cmax of both sofosbuvir and its metabolite.Conclusions Both atorvastatin and lovastatin increased AUC of sofosbuvir and its metabolite after concurrent administration with FDCSL. Statins’ P-glycoprotein inhibition is the attributed mechanism of interaction. The increase in sofosbuvir bioavailability was more pronounced after atorvastatin intake. Close monitoring is needed after co-administration of atorvastatin and FDCSL.
Keywords: Atorvastatin; Lovastatin; Ledipasvir; Sofosbuvir; GS-331007; P-glycoprotein